2020
DOI: 10.1155/2020/1397410
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Clinical vs. Digital Exophthalmometry Measurement Methods

Abstract: Background. A number of orbital diseases may be evaluated based on the degree of exophthalmos, but there is still no gold standard method for the measurement of this parameter. In this study we compare two exophthalmometry measurement methods (digital photography and clinical) with regard to reproducibility and the level of correlation and agreement with measurements obtained with Computerized Tomography (CT) measurements. Methods. Seventeen patients with bilateral proptosis and 15 patients with normal orbits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Proptosis is a significant way of diagnosing some orbital diseases and evaluating their severity and surgical indications. As mentioned above, the HE method of measuring proptosis is still the most common method used in clinic due to the popularization of equipment, simplicity of use, and being radiation-free, but the HE method has individual difference and poor repeatability, reducing the accuracy and credibility of the value (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proptosis is a significant way of diagnosing some orbital diseases and evaluating their severity and surgical indications. As mentioned above, the HE method of measuring proptosis is still the most common method used in clinic due to the popularization of equipment, simplicity of use, and being radiation-free, but the HE method has individual difference and poor repeatability, reducing the accuracy and credibility of the value (13).…”
Section: Discussionmentioning
confidence: 99%
“…However, professional software often means high cost. Digital photography is a simple and non-invasive alternative method that has been used to assess proptosis; however, a study has demonstrated that compared to clinical HE exophthalmometry, this method has greater variance and lower correlation with the radiological tool (13). Conversely, many different methods have been applied to evaluate the radiology method based on 3D CT images, and almost all studies have arrived at a similar conclusion: that the radiology method is accurate and reproducible to measure proptosis and exhibited a high correlation with the HE method.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years of research, some scholars measured the eyeball protrusion of TAO patients on the images obtained by CT scan, and they determined the most forward measurement position of the eyeballs by the the thickest position of the lens [ 9 , 10 ]. For TAO patients without myopathy, the CT slice of the thickest lens corresponds to the apex of the cornea, which is the most protruding position of the eyeball.…”
Section: Discussionmentioning
confidence: 99%
“…Errors in measurement are caused by thickness of subcutaneous tissue over the bone, facial asymmetry, parallax and examiner skills. 6,31 Apart from Hertel's exophthalmometer, a simple plastic scale at the lateral orbital margin, or a Luedde exophthalmometer, can be used. The latter is a thick plastic ruler with a notch to fit in the lateral orbital margin and markings in millimetres on both sides of the scale to avoid parallax.…”
Section: Investigations Primary Investigationsmentioning
confidence: 99%